Integration of Pancasila Student Profile in Islamic Religious Education Textbooks for Senior High School - Nasrudin, Ega; Rahmat, Munawar; Anwar, Saepul; Kosasih, Aceng; Fakhruddin, Agus; Firmansyah, Mokh. Iman (Eduprof : Islamic Education Journal, 2025)
The realization of students who have the Pancasila Student Profile is the goal of the current government. The rise of the three big sins of education, intolerance, and lack of discipline in the environment of elementary school students is a threat to the disintegration of basic education from within. The government is trying to present Pancasila Student Profile learning through various learning media, one of which is through the open book of PAI and Budi Pekerti. The novelty of this research is that it tries to find the values of the Pancasila student profile in PAI and character education textbooks. The purpose of this study is to examine the content of the Pancasila student profile in PAI textbooks used in high schools. This research method uses a qualitative design of literature study. The data sources of this study are divided into two categories: primary and secondary. Primary data sources come from the triangulation process of high school PAI student books, high school PAI teacher books, and regulatory documents regarding PAI learning in high school. While secondary data sources come from several relevant journals. The collected data were then analyzed in accordance with the stages of content analysis. The findings of this study indicate that Pancasila student profiles in PAI textbooks in high school have the most information, especially the dimensions of faith, devotion to God Almighty, and noble character. The values of each Pancasila student profile are explicitly and implicitly stated in each chapter of the PAI textbook. This study emphasizes that Islamic Religious Education, as one of the subjects mandated by the government, encourages the birth of students who have Pancasila student profiles. The implication of this research suggests that in the future teachers can find out the content of the Pancasila student profile in Islamic Education textbooks so that they can teach the content of the Pancasila student profile optimally